Raven nekaterih kazalcev vnetja in inflamatornih citokinov v serumu bolnikov s parodontalno boleznijo - Skalerič, Eva (Medicinski razgledi, 2004)
Periodontal disease is the most widespread disease of all chronic inflammatorydiseases. The initiation and development of inflammation in the periodontal tissue is influenced by the number and type of microorganisms and by the inflammatory immune host response. Analytical epidemiology and molecular biology studies in the last decade have shown that periodontal inflammation does not only present a risk for tooth loss, but may also play a role in the development of certain systemic diseases. Periodontal disease plays a role in development of some diseases via direct penetration of microorganisms into the bloodstream through an ulcerated inner gingival epithelium and by increasing the levels of some inflammatory mediators and cytokines in the serum. The aim of our study was to determine the levels of inflammatory mediators (C-reactive protein (CRP), fibrinogen, procalcitonin) and inflammatory cytokines (IL-2, sIL-2R, IL-6, IL-8, TNF-a) in the serum of systemically healthy blood donors with periodontal disease. Our hypothesis wasthat the size of soft periodontal pocket wall in contact with bacteria (infected periodontal wound) influences the level of inflammatory mediators and cytokines in the serum. For the evaluation of infected periodontal wounds,the cervical circumference was measured at the cemento-enamel junction on 515 extracted teeth. The average values of cervical circumferences of individual teeth were multiplied by the average values of six measurements of probing depth for individual teeth in 31 blood donors. The sum of all productsfor individual teeth presented the size of the infected periodontal wound for each individual. The sum of all products of periodontal pocket measurements, which bled on probing, presented the size of the active infectedperiodontal wound. (Abstract truncated at 2000 characters)
Keywords: Citokini; Periodontal Diseases; Parodontalne bolezni; Inflammation Mediators; Cytokines; Parodontalni žep; Blood; Vnetje, posredniki; Zobni vrat; Tooth Cervix; Periodontal Pocket; C-reaktivna beljakovina; Adult; Interlevkin-2; Interlevkin-6; Middle Age; Interlevkin-8; C-Reactive Protein; Fibrinogen; Kalcitonin; Calcitonin; Odrasli; Parodontalni indeks; Interleukin-2; Receptorji, interlevkin-2; Receptors, Interleukin-2; Srednja leta; Interleukin-6; Interleukin-8; Tumor nekrotizirajoči faktor; Tumor Necrosis Factor; parodontalna bolezen; Periodontal Index; vnetja